2012
DOI: 10.1002/ppap.201100186
|View full text |Cite
|
Sign up to set email alerts
|

The Diffusion‐reaction Model on the Wettability Gradient Created by SF6 Plasma

Abstract: Previously a model was reported on the simulation of a SF6 plasma generated wettability gradient by considering only the diffusion of the reactive species in plasma. This study proposed a modified model to describe the wettability gradient created by SF6 plasma by further considering the chemical reactions between the plasma species and the substrate. The wettability gradient was prepared by applying SF6 plasma on the O2 plasma pretreated polypropylene film that was covered with a mask. Experimentally, the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The water contact angle (WCA) and oil contact angle (OCA) indicate the hydrophobic and oleophilic properties of the membrane, respectively [38][39][40]. Membrane surface wettability was determined by measuring the static contact angles of liquid droplets [41,42]. In this study, the contact angles were determined by dropping 1 μL of deionized water and fresh oil, respectively, onto the membrane surface.…”
Section: = ( × ) × ( )mentioning
confidence: 99%
“…The water contact angle (WCA) and oil contact angle (OCA) indicate the hydrophobic and oleophilic properties of the membrane, respectively [38][39][40]. Membrane surface wettability was determined by measuring the static contact angles of liquid droplets [41,42]. In this study, the contact angles were determined by dropping 1 μL of deionized water and fresh oil, respectively, onto the membrane surface.…”
Section: = ( × ) × ( )mentioning
confidence: 99%
“…Fluorine-containing plasmas are often used for the surface hydrophobization of polymer materials [1,2,3,4,5,6,7,8] and for dry-etching in the semiconducting industry [9,10,11,12]. In the latter, the addition of oxygen is used to enhance the etching rate [11].…”
Section: Introductionmentioning
confidence: 99%
“…SF 6 is rarely used, and therefore, literature is scarce. SF 6 plasma has been used to treat polyethylene terephthalate PET (fabric [1], fibres [7] or film [5]), cotton fibres [7], polypropylene (PP) [3,4], polyethylene (PE) [5], polyvinyl chloride (PVC) [5] and polymethyl methacrylate [2]. The authors reported increased hydrophobicity; however, different authors reported different stabilities of the hydrophobic surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a substrate is covered with a one‐end open mask, a constant diffusion rate of the plasma reactive species is obtained . Mangindaan et al started to determine the mechanism related to the production of lateral gradients onto polypropylene substrates using such a mask in the static configuration. A model consisting of three sub‐processes was proposed: 1) bulk diffusion of the plasma reactive species; 2) interfacial adsorption/desorption; and 3) surface chemical reactions.…”
Section: Introductionmentioning
confidence: 99%